ENZYMATIC STUDY OF FRESH WATER MACRO AND MICRO ALGAE ISOLATED FROM JALGAON, MAHARASHTRA - KISHORE.J. PATIL,; R.T.MAHAJAN, (International Journal of Pharma and Bio Sciences, 2016)
The phenotypic, phylogenetic, geographical diversity and sustainability ability of micro-algae capable of producing enzymes provides a challenge for the accurate determination of biotechnological potential. For production of economically important products like agar, alginates, biodiesel, bio-fuel and medicinally important products algae extensively employed. Although, so lengthily for enzyme production. The modified methods developed to facilitate fast and reliable screening of enzyme production. Experiments carried out on nine macro algae and ten micro-algal strains isolated from Jalgaon region, Maharashtra (India) and two micro-algal strains obtained from BIT Ranchi, an approach found to provide a more reliable measure for enzyme production. Out of 21 algae, 5 strains are positive for lipase, 20 for phosphatase, 06 for amylase, 07 for gelatinase, 05 for urease and 19 for catalase. This is an important escalation for isolation and screening of enzyme production from microalgae.